Examining the Threat of Terrorism in South Asia: A Case Study of India and Pakistan - Waqas, Muhammad; Afzal, Faiza; Ali, Sania Sher (Annals of Human and Social Sciences, 2024)
This research examines the threat of terrorism in South Asia, with a focus on India and Pakistan. The objective is to analyse the impact of terrorism on regional security and stability. As far as the history of both countries and their geopolitics is concerned, terrorism has remained an active and essential hazard. The study employs a qualitative approach, including a review of existing literature and policy analysis. The results reveal that terrorism significantly undermines regional stability, exacerbates tensions between India and Pakistan, and poses a persistent threat to national and international security. The study finds that both countries face challenges in effectively combating terrorism due to political complexities and socio-economic factors. It is recommended that bilateral cooperation be enhanced, comprehensive counter-terrorism strategies be implemented, and international partnerships be established to address the root causes of terrorism and improve regional security.